The dual standard model and the 750 GeV events at the LHC. (22nd August 2016) - Calmet, Xavier
Abstract: The aim of this letter is to discuss the recently observed excess at 750 GeV by both CMS and ATLAS in the light of the dual standard model. Within this framework it is natural to introduce neutral spin-0 and/or spin-2 SU (2) glue mesons which could easily account for this observation if it is confirmed. The model predicts that these glue mesons would be part of SU (2) triplets and that there must thus be charged counterparts of these glue mesons carrying a QED charge of ±1 with a spin 0 and/or 2 as well.